The BRI: Trade integration and stock market synchronization. A review of empirical findings - Alexander Heß; Christoph Michael Hindermann (OrdnungsPolitisches Portal (OPO), 2022)
In the context of the Belt and Road Initiative (BRI), we review selected studies that explicitly or implicitly address the question of whether there occurs synchronization of stock markets between China and the BRI economies. Following this, we examine the extent to which this synchronization of stock markets may be driven by bilateral trade. This question is of particular interest to investors who wish to profit from the BRI while minimizing their risk through portfolio diversification. Our results show that there is plenty of supporting evidence that the stock markets of China and the BRI economies are synchronized, and that synchronization appears to be increasing since the launch of the BRI. We also find that bilateral trade is an important determinant for explaining stock market integration between China and the BRI countries. Based on these results, interregional diversification appears to be less efficient. Further research is needed to determine whether other forms of diversification, such as inter-industry diversification, would be more beneficial.
Keywords: 330; BRI; Belt and Road Initiative; Belt and Road Countries; China; Stock Market Synchronization; Stock Market Co-Movement; Stock Market Integration; Trade Integration; Trade Volume; Bilateral Trade; Portfolio Diversification; Investing